Neurobrucellosis Accompanied by Sternoclavicular Arthritis: A Case Report - Hatice Köse; Fatih Temoçin; Serap Temoçin (Haseki Tıp Bülteni, 2017)
Brucellosis is a zoonotic infectious disease. It may show several manifestations and involve several systems, such as cardiovascular, hematopoietic, skeletal, nervous, and gastrointestinal systems and the skin. Sternoclavicular arthritis and prostatitis caused by brucellosis are rare conditions, which have been reported previously as case presentations in the literature. In this article, we present a case of neurobrucellosis accompanied by sternoclavicular arthritis and prostatitis to highlight that the disease may manifest with several signs and symptoms with rare involvements.